Future teachers' reflection on the inclusion of sexual and gender diversity - Sánchez, Begoña Torrejón; Brazão, Paulo; Dias, Alfrancio Ferreira; Mendonça, Alice (Revista Labor, 2022)
The aim of this paper is to discuss the inclusion of gender diversity in teacher education, as well as the possibilities and suggestions for initiatives to be developed in the field of immediate, middle and long distance education. Methodologically, I studied a qualitative approach, based on the input of second year students of Early Childhood Education at the University of Cadiz, Spain, through open group interviews about their conceptions of sexual and gender diversity and how to develop inclusion. diversity and gender in the academic context. We analysed and discussed two categorised data forums: 1) Concept of inclusion of gender diversity; 2) Characterisation of the current Spanish educational system in relation to the inclusion of gender diversity; 3) Who, where and how inclusion should be worked on; 4) Actions to be developed by tutors; 5) Proposals for the approach to the inclusion of gender diversity. It is concluded that a transversal, systematic and continuous work is necessary for the inclusion of sexual and gender diversity in all academic contexts, with educational actions that provide moments of listening to LGBTQIA+ students and their families.